The Prime Filter Theorem for Multilattices - Daquin Cédric Awouafack; Blaise Blériot Koguep Njionou; Célestin Lélé (International Journal of Mathematics and Mathematical Sciences)
The aim of this paper is to establish the prime filter theorem for multilattices.